Gestão de resíduos sólidos : estudo de caso da Companhia Vale do Rio Doce (CVRD), Rosário do Catete/ SE - Silva, Isabel Cristina Barreto (2008)
With the objective of making a behavioural diagnostic analysis in an ore organization concerning environmental questions, and mainly to understand the way the knowledge on environment is transfered, we researched the Vale do Rio Doce company, with the intention of obtain information about the procedures taken concerning the solid wastes disposal, what measures of environmental impact reduction are adopted and how its staff is trained. In this sense, a bibliographical research was carried out and also a diagnostic of the perception which the managers and their colaborators have about the environment matters. Thus, questions such as environmental education, sustainable development, environmental impacts, reducing measures and solid waste management were raised. The results showed that the company is significantly concerned with the correct solid waste disposal in its main operational nuclei (mine and plant) nor only because of legislation but also because of environmental questions. During the interviews, it was noticed that the employees have a significant critical consciousness that the correct waste disposal will offer security and comfort to them as well as an ethical conduct towards the environment and society.